On nilpotent filiform Lie algebras of dimension eight - P. Barbari; A. Kobotis (International Journal of Mathematics and Mathematical Sciences)
The aim of this paper is to determine both the Zariski constructible set of characteristically nilpotent filiform Lie algebras g of dimension 8 and that of the set of nilpotent filiform Lie algebras whose group of automorphisms consists of unipotent automorphisms, in the variety of filiform Lie algebras of dimension 8 over C.